Do Career-Engaging Courses Engage Low-Income Students?. (October 2021) - Plasman, Jay Stratte; Gottfried, Michael A.; Klasik, Daniel J.
Encouraging school engagement is crucial to promoting positive outcomes for high school students. One potential means to promote school engagement may be through career and technical education (CTE) coursework, which is specifically designed to be educationally engaging, particularly for vulnerable populations such as those from low-income backgrounds. Yet, little is known about whether these courses do in fact link to higher school engagement. Through analysis of the High School Longitudinal Study of 2009—a nationally representative data set—we explored the link between STEM-focused CTE (STEM-CTE) coursetaking and school engagement for low-income students. To do so, we employed an instrumental variable estimation technique and found that taking STEM-CTE courses related to higher school engagement for low-income students. We conclude with a discussion of implications for students, practitioners, and policymakers.